Heritability and circulating concentrations of pregnancy-associated plasma protein-A and stanniocalcin-2 in elderly monozygotic and dizygotic twins - Hjortebjerg, Rikke; Pedersen, Dorthe Almind; Mengel-From, Jonas; Jørgensen, Louise Helskov; Christensen, Kaare; Frystyk, Jan (Frontiers in Endocrinology, 2023)
Introduction. Pregnancy-associated plasma protein-A (PAPP-A) is an IGF-activating enzyme suggested to influence aging-related diseases. However, knowledge on serum PAPP-A concentration and regulation in elderly subjects is limited. Therefore, we measured serum PAPP-A in elderly same-sex monozygotic (MZ) and dizygotic (DZ) twins, as this allowed us to describe the age-relationship of PAPP-A, and to test the hypothesis that serum PAPP-A concentrations are genetically determined. As PAPP-A is functionally related to stanniocalcin-2 (STC2), an endogenous PAPP-A inhibitor, we included measurements on STC2 as well as IGF-I and IGF-II. Methods. The twin cohort contained 596 subjects (250 MZ twins, 346 DZ twins), whereof 33% were males. The age ranged from 73.2 to 94.3 (mean 78.8) years. Serum was analyzed for PAPP-A, STC2, IGF-I, and IGF-II by commercial immunoassays. Results. In the twin cohort, PAPP-A increased with age (r=0.19; P<0.05), whereas IGF-I decreased (r=-0.12; P<0.05). Neither STC2 nor IGF-II showed any age relationship. When analyzed according to sex, PAPP-A correlated positively with age in males (r=0.18; P<0.05) and females (r=0.25; P<0.01), whereas IGF-I correlated inversely in females only (r=-0.15; P<0.01). Males had higher levels of PAPP-A (29%), STC2 (18%) and IGF-I (19%), whereas serum IGF-II was 28% higher in females (all P<0.001). For all four proteins, within-pair correlations were significantly higher for MZ twins than for DZ twins, and they demonstrated substantial and significant heritability, which after adjustment for age and sex averaged 59% for PAPP-A, 66% for STC2, 58% for IGF-I, and 52% for IGF-II. Discussion. This twin study confirms our hypothesis that the heritability of PAPP-A serum concentrations is substantial, and the same is true for STC2. As regards the age relationship, PAPP-A increases with age, whereas STC2 remains unchanged, thereby supporting the idea that the ability of STC-2 to inhibit PAPP-A enzymatic activity decreases with increasing age.